Taxonomic identity of Molineria garoense and lectotypification of Hypoxis trichocarpa (Hypoxidaceae) - Tiwari, Arjun Prasad (Phytotaxa, 2020)
Molineria garoense (Hypoxidaceae) described from Garo Hills, Meghalaya, India is treated here as a synonym of highly variable species Molineria trichocarpa. Besides, a lectotype is also designated for the name Hypoxis trichocarpa in the present paper.